New species and subspecies of Laoechinophorus from China and Thailand (Coleoptera, Cerambycidae, Lamiinae, Morimopsini) - Yamasako, Junsuke; Vives, Eduard; Liu, Bin (Zootaxa, 2021)
Two new species with a new subspecies of the genus Laoechinophorus Gouverneur, 2016 are described: L. thailandicus thailandicus ssp. nov. and L. thailandicus tsuyukii ssp. nov. from Thailand, and L. yunnanus sp. nov. from China. A description of male genitalia of the type species, L. unifasciatus Gouverneur, 2016, from Laos, and a key to the species of the genus are provided.